83.6k views
2 votes
Y = -3x+4 and y= 1/2x-3

User FLBKernel
by
4.9k points

1 Answer

3 votes

Answer:

{x = 2 , y = -2

Explanation:

Solve the following system:

{y = 4 - 3 x | (equation 1)

{y = x/2 - 3 | (equation 2)

Express the system in standard form:

{3 x + y = 4 | (equation 1)

{-x/2 + y = -3 | (equation 2)

Add 1/6 × (equation 1) to equation 2:

{3 x + y = 4 | (equation 1)

{0 x+(7 y)/6 = (-7)/3 | (equation 2)

Multiply equation 2 by 6/7:

{3 x + y = 4 | (equation 1)

{0 x+y = -2 | (equation 2)

Subtract equation 2 from equation 1:

{3 x+0 y = 6 | (equation 1)

{0 x+y = -2 | (equation 2)

Divide equation 1 by 3:

{x+0 y = 2 | (equation 1)

{0 x+y = -2 | (equation 2)

Collect results:

Answer: {x = 2 , y = -2


User Mahboudz
by
4.9k points